Cultural adaptation and reliability assessment of the Hammersmith neonatal neurological examination for Brazilian newborns at risk of cerebral palsy - Correr, Mayara Thais; Pfeifer, Luzia Iara (Arquivos de Neuro-Psiquiatria, 2023)
Background Reliable instruments that lead to early diagnosis for CP are extremely important so that these children are referred for early stimulation, benefiting their development.Objective To perform a cross-cultural adaptation and reliability assessment of a Brazilian version of the Hammersmith Neonatal Neurological Examination (HNNE), expanded and summarized.Methods A methodological, cross-sectional, nonexperimental quantitative analysis was conducted in two phases as follows: cultural adaptation of the HNNE, expanded and summarized, and reliability assessment of the Brazilian version of the HNNE. Phase one was developed in five stages (initial translation, synthesis of the translation, a committee of experts, backtranslation, and submission to the author), with the semantic questions, content, and face validity being evaluated. Phase two included 143 newborns and we analyzed the internal consistency, stability, and equivalence (intra- and interexaminer) of the instrument. Internal consistency was calculated using Cronbach's alpha, and intra- and interexaminer reliability and reproducibility assessed through test-retest were calculated using the intraclass correlation coefficientResults Although internal consistency, assessed using Cronbach's alpha, showed unsatisfactory results, the results of inter-and intraexaminer equivalence showed a high agreement between the evaluations in all domains. The test-retest also showed excellent agreement between the domains.Conclusions The Brazilian HNNE expanded and summarized versions can be considered to be adapted and reliable for the neurological assessment of Brazilian newborns to identify changes in neurological development and early referral to the stimulation or early rehabilitation units and as a promising option to be used in the context of primary care in Brazil.
Keywords: Cerebral Palsy; Early Diagnosis; Neurology